PERBANDINGAN HASIL RIAS FANTASI TEMA FLORA DENGAN TEKNIK MANUAL DAN TEKNIK AIRBRUSH - DHIYA PEBRINA PEBRINA; Murni Astuti (Jurnal Tata Rias dan Kecantikan, 2022)
This study aims to see the difference in the effect of the flora theme fantasy make-up with manual techniques and airbrush techniques. This type of research is experimental. The research sample was 4 people. The analysis technique uses descriptive statistical techniques. The data collection technique was purposive sampling. Descriptive data analysis techniques by displaying the mean, standard deviation, minimum, and maximum values. Bivariate analysis using independent-sample ttest with a confidence degree of 90%. The results of the flora theme fantasy make-up using manual techniques based on statistical calculations, it was found that the highest value was in the flatness aspect of the results, namely 2.64 which had fine criteria, time efficiency had 2.57 with fast criteria, and color sharpness had a value of 2.21 with sharp criteria. Meanwhile, the results of the flora theme fantasy make-up  using the airbrush technique based on statistical calculations, it was found that the highest value was in the aspect of time efficiency and the flatness of the results with a value of 3.71 having very fast and very smooth criteria, on the aspect of color sharpness it had an average of 3.64 with very sharp criteria. There are differences in the results of fantasy makeup on flora themes using manual techniques and airbrush techniques in the aspect of time efficiency (p = 0.000), on the aspect of flatness of the results (p = 0.000), and on the aspect of color sharpness (p = 0.000).